Living donor liver transplantation for obese patients: Challenges and outcomes. Issue 3 (13th January 2014) - Gunay, Yusuf; Guler, Necdet; Dayangac, Murat; Taskesen, Fatih; Yaprak, Onur; Emek, Ertan; Akyildiz, Murat; Altaca, Gulum; Yuzer, Yildiray; Tokat, Yaman
<x xml:space="preserve">Abstract</x> Living donor liver transplantation (LDLT) is an accepted option for end‐stage liver disease, particularly in countries in which there are organ shortages. However, little is known about LDLT for obese patients. We sought to determine the effects of obesity on pretransplant living donor selection for obese recipients and their outcomes. On the basis of body mass index (BMI) values, 148 patients were classified as normal weight (N), 148 were classified as overweight (OW), and 74 were classified as obese (O). O recipients had significantly greater BMI values (32.1 ± 1.6 versus 23.2 ± 1.9 kg/m2, P < 0.001) and received larger actual grafts (918.9 ± 173 versus 839.4 ± 162 g, P = 0.002) than recipients with normal BMI values. Donors who donated to O recipients had a greater mean BMI (26.3 ± 3.8 kg/m2) than those who donated to N recipients (24.4 ± 3.2 kg/m2, P = 0.001). Although O recipients were more likely to face some challenges in finding a suitable living donor, there were no differences in graft survival [hazard ratio (HR) = 0.955, 95% confidence interval (CI) = 0.474‐1.924, P = 0.90] or recipient survival (HR = 0.90, 95% CI = 0.56‐1.5, P = 0.67) between the 3 groups according to an adjusted Cox proportional hazards model. There were no significant differences in posttransplant complication rates between the 3 recipient groups or in the morbidity rates for the donors who donated to O recipients versus the donors who donated to OW and N recipients (P = 0.26). Therefore, we recommend that obese patients undergo pretransplant evaluations. If they are adequately evaluated and selected, they should be considered for LDLT. Liver Transpl 20:311‐322, 2014. © 2013 AASLD.